Determined tomato cultivars with ecological stress resistance for growing in open field condition - I.U. Kondratieva; E.E. Kandoba (Овощи России, 2008)
In north regions of Russia the breeding programs are manly focused on developing tomato cultivars with following characteristics: resistance to stresses (biotic, abiotic), high yield capacity, high quality output, high dry matter content and long storage ability of tomato fruits. Since 2007 in State Registry of Plant Breeding Achievements there are three cultivars Malinka, Rosinka, Unona bred at All-Russian Research Institute of Vegetable Breeding and Seed Production that were included. Their high ecological plasticity provides a stable yield under any climatic condition of a year.